Anti-convulsant effects of cultures bear bile powder in febrile seizure via regulation of neurotransmission and inhibition of neuroinflammation. (15th November 2020) - Sun, Xiaoshu; Xue, Haoyu; Zan, Bin; Zhao, Yining; Li, Yuanyuan; Wang, Tianming; Wu, Jiasheng; Liu, Shaoyong; Wang, Zhengtao; Shi, Rong; Yang, Li; Ma, Yueming
Abstract: Ethnopharmacological relevance: Natural bear bile powder (NBBP) has been used to treat seizures for thousands of years, but its application is greatly restricted due to ethical reasons. Cultured bear bile powder (CBBP), which is produced by biotransformation, may be an appropriate substitute for NBBP. However, the anti-convulsant effects of CBBP and its mechanisms remain unclear. Aim of the study: This study aimed to investigate the anti-convulsant effects and possible mechanisms of CBBP in a febrile seizure (FS) rat model. Materials and methods: FS was induced by placing the rats in a warm water bath (45.5 °C). The incidence rate and latency of FS, and hematoxylin-eosin staining (HE) were conducted for neurological damage. The levels of 4 bile acids and 8 main neurotransmitters in vivo were measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The expression of bile acid related transports, neurotransmitter receptors, inflammatory factors, neurotrophic factors and glial fibrillary acidic protein (GFAP) in hippocampal tissues were detected by real-time PCR, western blotting, and immunohistochemistry. Results: Pre-treatments with CBBP and similarly, NBBP, significantly reduced the incidence rate and prolonged the latency of FS. Additionally, CBBP alleviated the histological injury induced by FS in the rat hippocampus tissue. LC-MS/MS analyses revealed that CBBP markedly increased the levels of tauroursodeoxycholic acid (TUDCA), taurochenodeoxycholic acid (TCDCA), ursodeoxycholic acid (UDCA), and chenodeoxycholic acid (CDCA) in FS rats. Furthermore, the content of gamma-aminobutyric acid (GABA) was up-regulated in rats pre-treated with CBBP whereas GFAP was down-regulated. CBBP also significantly suppressed the expression of interleukin -1β (IL-1β), tumor necrosis factor α (TNF-α), nuclear factor kappa B (NF-κB), and brain-derived neurotrophic factor (BDNF) and its TrkB receptors, and improved the expression of GABA type A receptors (GABAA R) and farnesoid X receptors (FXR). Conclusions: The present study demonstrated that CBBP had anti-convulsant effects in a FS rat model. CBBP may protect rats against FS, probably by up-regulating FXR, which was activated by increasing brain bile acids, up-regulating GABAergic transmission by inhibiting BDNF-TrkB signaling, and suppressing neuroinflammation by inhibiting the NF-κB pathway. Graphical abstract: Image 1